(untitled) (American Journal of Islam and Society, 2003)
The author, who embraced the teachings of Louis Farrakhan’s revamped Nation of Islam (NOI) in the late I 970s to find solutions to America’s race problems, left disillusioned in the mid-1990s. What he witnessed as he passed through the organization’s rank and file compelled him to compile his experiences to give others a clearer understanding of the Nation’s origins as well as its role concerning the issues facing African-Americans. Inside the Nation of Islam is divided into I I chapters and contains a foreword by Mike Wallace an epilogue by the author, extensive notes, a bibliography, and an index. Also included are several photographs that illustrate White’s extensive involvement in the NOL With a brief overview of African-American history prior to the NOI’s creation, chapters 1 and 2 touch on the Harlem Renaissance, the origin of the Jim Crow laws, and the mass exodus of African-Americans from the South to the North. With the fall of similar resistance movements, the NOJ stepped in to address the bitter disillusionment that many of them experienced upon their arrival in the North ...